A Dynamic Assessment of Children’s Physical Competence: The Dragon Challenge - TYLER, RICHARD (Med Sci Sports Exerc, 2018)
PURPOSE: The first aim was to develop a dynamic measure of physical competence that requires a participant to demonstrate fundamental, combined and complex movement skills, and assessors to score both processes and products (Dragon Challenge [DC]). The second aim was to assess the psychometric properties of the DC in 10- to 14-yr-old children. METHODS: The first phase involved the development of the DC, including the review process that established face and content validity. The second phase used DC surveillance data (n = 4355; 10–12 yr) to investigate construct validity. In the final phase, a convenience sample (n = 50; 10–14 yr) performed the DC twice (1-wk interval), the Test of Gross Motor Development-2 (TGMD-2), and the Stability Skills Assessment (SSA). These data were used to investigate concurrent validity, and test–retest, interrater and intrarater reliabilities. RESULTS: In support of construct validity, boys (P < 0.001) and secondary school children (P < 0.001) obtained higher DC total scores than girls and primary school children, respectively. A principal component analysis revealed a nine-component solution, with the three criteria scores for each individual DC task loading onto their own distinct component. This nine-factor structure was confirmed using a confirmatory factor analysis. Results for concurrent validity showed that there was a high positive correlation between DC total score and TGMD-2 and SSA overall score (r(43) = 0.86, P < 0.001). DC total score showed good test–retest reliability (intraclass correlation coefficient = 0.80; 95% confidence interval, 0.63, 0.90; P < 0.001). Interrater and intrarater reliabilities on all comparison levels was good (all intraclass correlation coefficients > 0.85). CONCLUSION: The DC is a valid and reliable tool to measure elements of physical competence in children age 10 to 14 yr.